Person-Environment Fit: Concept, Importance, Types, and Consequences A Descriptive Study - Alharbi, Abdullah Medari (The Arab Journal of Administration, 2024)
While individuals are keen to obtaining jobs meet their needs, and are in line with their aspirations and goals, organisations, on the other hand, make great efforts to attract those who are fit with their jobs’ requirements, goals, and values. In this regard, studies of person-environment (work environment) fit focus on building and sustaining a good fit between individuals and such environment. Although this new field of research is a central topic in the Western literature, the Arabic literature still so far suffers from a clear deficiency in theorizing such topic philosophically, conceptually, and methodologically, exploring its dimensions, and revealing its multiple relationships and influences. Therefore, the current study sought to define the phenomenon of person-environment fit from several aspects, by achieving three main objectives. First, to introduce the most prominent aspects of the phenomenon, such as its conceptual roots, the beginning theoretical construction, the historical development, the most prominent principles, the importance of studying such phenomenon, and its types and levels. Second, to focus on its consequences within the work environment, its measurements, its weaknesses, and scholars’ efforts to develop this topic. Third, to contribute and enrichment the Arabic literature by providing a new theoretical framework to this vital field. To achieve these objectives, the study used descriptive approach. The study concluded that selection of individuals for appropriate jobs for them in recruitment stage leads to good fit between persons and work environment, and such process enhances organisations to maintaining their human resources. Further, it positively affects their behaviour and attitudes, and even more their family and public life. Finally, the study posted a number of theoretical and practical recommendations in order to support researchers and practitioners towards achieving good fit in the work environment.